PENGARUH FASILITAS BELAJAR DI RUMAH DAN MINAT BELAJAR TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS XI IPS SMA NEGERI 4 KUNDUR - Tri Jumiawati; Suarman Suarman; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of learning facilities at home and interest on student learning motivation in Economics in class XI Ips SMA Negeri 4 Kundur. The background of this research is the student's learning motivation which is still low in the Economics subject. This research was conducted on class XI Ips SMA Negeri 4 Kundur with a total student population of 89 students. In this study, using a saturated sampling technique (census), in which the entire population was sampled because the population was less than 100. Primary data were collected using a questionnaire containing questions to measure learning motivation, learning facilities at home and interest in learning which were distributed to class XI Ips SMA Negeri 4 Kundur as respondents. Meanwhile, secondary data is in the form of data on school profiles which was carried out in April 2019/2020 odd semester at SMA Negeri 4 Kundur. The data collected was then tabulated and analyzed using multiple linear regression with the help of SPSS version 22. The results showed that learning facilities and interest in learning had an effect on student learning motivation in class XI Ips SMA Negeri 4 Kundur with the regression equation Y = 15,924 + 0,535 x1 + 0.864x2 and contributes to student learning motivation by 36%.Key Words: Factors, Learning Interests, Learning Facilities At Home, Learning Motivation